POTENCY OF PICUNG (Pangium edule Reinw) ENDOSPERM UTILIZED AS A RAW MATERIAL IN PRODUCINGFRYING OIL OR BIODIESEL - Farida Hanum Hamzah; Nirwana Hamzah; Irdoni HS (BPFP Faperta UNIB, 2018)
This research aimed to know Picung/ Pangi (Pangium Edule Reinw) plant's potencies as raw material for frying oil and biodiesel alternative so that it can be used as extensive as palm and coconut oil. As this picung/pangi plants are widely consumed by Indonesian people, this plant is an interesting subject to be researched and studied on. The result of this research will be a great reference in increasing the utilization of Pangi Plant. The research method that is being used in this research for frying oil production is extraction using petroleum eter in laboratory scale and the yield then analyzed. The results presented shown that the density: 0.918 g/ml; water content: 0.0253%; free fatty acid (FFA) content: 2.53%; fat content: 51.468%; acid number: 0.33 mg KOH/g; Iodine number: 29.31 g Iod/100 g Oil; peroxide number: 4.124 meq/kg; and oil's color depends on the process used. The oil produced was then used for making biodiesel, which consist of two-step processes, esterification and transesterification. The result of this research shown that characteristics of biodiesel produced as follow: density: 0.888 g/ml; viscosity: 0.0006 g/cms; water content: 0.024%; free fatty acid (FFA) 0.3557%; Iodine number: 29.31 g Iod / 100 g Oil; scap number: 188.23 mg KOH/g; acid number 0.33 mg KOH/g; and Cetane number was 68.7. It is concluded that Picung/Pangi oil can be used as frying oil and biodiesel as an alternative fuel.